An aerobic oxidation of alcohols into carbonyl synthons using bipyridyl-cinchona based palladium catalyst. Issue 52 (6th October 2021) - Cheedarala, Ravi Kumar; Chidambaram, Ramasamy R.; Siva, Ayyanar; Song, Jung Il
Abstract : We have reported an aerobic oxidation of primary and secondary alcohols to respective aldehydes and ketones using a bipyridyl-cinchona alkaloid based palladium catalytic system (PdAc-5 ) using oxygen at moderate pressure. Abstract : We have reported an aerobic oxidation of primary and secondary alcohols to respective aldehydes and ketones using a bipyridyl-cinchona alkaloid based palladium catalytic system (PdAc-5 ) using oxygen at moderate pressure. The PdAc-5 catalyst was analysed using SEM, EDAX, and XPS analysis. The above catalytic system is used in experiments for different oxidation systems which include different solvents, additives, and bases which are cheap, robust, non-toxic, and commercially available on the industrial bench. The obtained products are quite appreciable in both yield and selectivity (70–85%). In addition, numerous important studies, such as comparisons with various commercial catalysts, solvent systems, mixture of solvents, and catalyst mole%, were conducted using PdAc-5 . The synthetic strategy of oxidation of alcohol into carbonyl compounds was well established and all the products were analysed using 1 H NMR, 13 CNMR and GC-mass analyses.